Estudo do processo de eletrofiação de micro/nanofibras de polímeros biodegradáveis para liberação do antibiótico Cloxacilina - Schneider, Rodrigo (Universidade Federal de São Carlos, 2018)
Bovine mastitis disease is caused by some class bacteria and fungus from the environment, which affects the dairy cattle herd. This disease can cause financial damage to farmers by reducing cattle milk production. In this work we developed biodegradable flexible polymer mats added with antibiotic aiming at producing antibiotic release systems for use topical against Gram-positive bacteria that causes mastitis. The electrospinning technique was employed to produce the micro/nanofibers, which the antimicrobial activity was promoted by the addition of the b-lactam antibiotic Cloxacillin (CLOX) in polymer solution. PBAT (poly(butylene adipate-co-terephthalate)/PLA (poly(lactic acid)) blend fibers with CLOX (ECNF_CLOX) were characterized by FTIR spectroscopy, scanning electron microscopy (SEM), contact angle, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and X-Ray photoelectron spectroscopy (XPS). Release kinetics were performed in buffered solutions of pH = 7.3 and pH = 5.5. Quantitative determination of the released CLOX concentration was monitored by high performance liquid chromatography (HPLC). The results showed rapid release kinetics at pH = 7.3 and prolonged release at pH = 5.5. The mean release capacity was 70% at neutral pH and only 14% at acidic pH. This rapid release is in accordance with the arrangement of the drug according to XPS technique, suggesting that the drug distribution is close to the surface of the fibers. Microbiological essay against S. aureus indicated the bactericidal and bacteriostatic effects of CLOX-containing fibers, suggesting its potential for designing drug release systems.
Study of electrospinning process of biodegradable polymers micro/nanofibers for Cloxacillin antibiotic release
Keywords: Cloxacilina; Liberação fármacos; Nanofibras de polímeros; Eletrofiação; Electrospinning; Cloxacillin; Drug release; Antimicrobial nanofibers; PLA; PBAT; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA